Supra-Annular Versus Intra-Annular Self-Expanding Valves in Small Aortic Annulus: A Propensity Score-Matched Study - Michel Pompeu Sá, MD, MSc, MHBA, PhD; Danial Ahmad, MD, MPH; Yisi Wang, MPH; Floyd Thoma, BS; Amber Makani, MD; Dustin Kliner, MD; Catalin Toma, MD; David West, MD; Derek Serna-Gallegos, MD; Ibrahim Sultan, MD (Structural Heart)
Background: Transcatheter aortic valve replacement (TAVR) with self-expanding valves (SEVs) may have different outcomes with supra-annular valves (SAVs) or intra-annular valves (IAVs) in patients with small aortic annuli (SAA), but this topic remains underexplored. We aimed to evaluate outcomes between different SEVs, namely SAVs (CoreValve/Evolut R/PRO/PRO+/FX) vs. IAVs (Portico/Navitor). Methods: Single-center data with patients with SAA (maximum diameter <23 mm) who underwent TAVR from 2013 to 2023 with SEVs, followed by 1:1 propensity score matching (PSM). Results: We obtained 86 PSM pairs with median age of 83.0 years (SAVs) and 82.0 years (IAVs), with women representing 77.6% of the PSM cohort. After TAVR, we did not find statistically significant differences for the following outcomes: Valve Academic Research Consortium-3 periprocedural mortality, technical success, device success, clinical efficacy, and rates of paravalvular leak were not statistically significantly different, but we found higher rates of permanent pacemaker implantation in the IAV group (1.2 vs. 8.1%; p = 0.029). Despite the larger indexed effective orifice area with SAVs (median 1.0 vs. 0.8 cm2/m2, p = 0.001), we did not find statistically significant differences between the groups in terms of residual mean gradients >20 mmHg (0.0 vs. 2.3%, p = 0.155), and severe prosthesis-patient mismatch (2.3 vs. 5.8%, p = 0.390). No statistically significant difference was observed in survival (log-rank p = 0.950) and stroke (p = 0.6547) between patients who received SAVs and IAVs. For patients with SAA, TAVR with SEV devices is safe. Conclusions: IAVs and SAVs are associated with comparable device performance in terms of hemodynamic structural and nonstructural dysfunction. Randomized data are needed to validate these findings and guide informed device selection.